Pengaruh Metode Snowball Throwing Pada Model Pembelajaran Discovery Terhadap Hasil Belajar Peserta Didik Kelas X Mia Man 1 Sidrap (Studi Pada Materi Pokok Sistem Periodik Unsur) - Muniratuzahra, Muniratuzahra; Salempa, Pince; Ramdani, Ramdani (Jurusan Kimia FMIPA UNM, 2021)
This research aims to determine the effect of the snowball throwing method on the discovery learning model of students learning outcomes in the subject matter of the Periodic System of Elements. The Research Population of all students in X MIA MAN 1 SIDRAP, period 2018/2019. The sample of 29 people in class X MIA 2 as an experimental group was taught by the snowball throwing method in the discovery learning model and 29 people in class X MIA 1 as a group control that was learned by the discovery learning model without the snowball throwing method. Data collection through student learning outcomes and questionnaire responses to research design posttest control group design. The results of the descriptive analysis showed that the average value of the experimental group using the snowball throwing method on the discovery learning model, it was higher at 73.05 compared to the control group which only used the discovery learning model without the snowball throwing method which was 69.74. The results of hypothesis testing on inferential statistics using the Mannwhitney test obtained a Zhitung value of 3.62 and at the confidence level (α) of 0.05 obtained Ztable 1.65. Therefore, Zhitung> Ztable then H0 is rejected and H1 is accepted, it shows that there is a significant effect of using the snowball throwing method on the discovery learning model on the learning outcomes of class X MIA MAN 1 SIDRAP in the subject matter of the periodic system element.